Hypoxia effects on oxidative stress and immunocompetence biomarkers in the mussel Perna perna (Mytilidae, Bivalvia). (May 2017) - Nogueira, Lílian; Mello, Danielle Ferraz; Trevisan, Rafael; Garcia, Danielly; da Silva Acosta, Daiane; Dafre, Alcir Luiz; de Almeida, Eduardo Alves
Abstract: This study investigated the effects of hypoxia on oxidative stress response and immune function in mussels Perna perna exposed to air for 6, 12, 24 and 48 h. In air-exposed mussels, the antioxidant enzymes superoxide dismutase (SOD), catalase, and glutathione reductase (GR) activities were lower in gill tissues (24–48 h) and digestive gland (12 h), while the glutathione peroxidase and GR activities were increased in the digestive gland (48 h). In both tissues, aerial exposure promoted a rapid (6 h) and persistent (up to 48 h) increase of glutathione levels. Decreased hemocyte count and viability, as well as increased phagocytic activity and cellular adhesion capacity were detected after prolonged aerial exposure (>12 h). In summary, induction of thiol pools, altered antioxidant enzyme activities, and activation of immune responses were detected in hypoxia exposed brown mussels, indicating hypoxia induced tissue-specific responses in both antioxidant and immune systems. Highlights: Brown mussels Perna perna were exposed to air for 6, 12, 24 and 48 h. Air exposure modulated antioxidant enzyme activities after 12 h. Hypoxia increased glutathione levels in gills and digestive gland as fast as 6 h. Hemocytes were sensitive to hypoxia, suggesting marked effects on the immune system. Prolonged hypoxia may affect the resistance to oxidative stress and pathogens.